RXR: A new X‐ray facility at XLab Frascati1. (24th April 2015) - Hampai, D.; Liedl, A.; Polese, C.; Cappuccio, G.; Dabagov, S.B.
<x xml:space="preserve">Abstract</x> X‐ray fluorescence analysis is a widely used technique in many applications. Recent advances in X‐ray optics, in particular, in polycapillary manufacturing, have allowed achieving microscale spatial resolution, even with conventional sources. Nowadays, many apparatus for X‐ray microfluorescence are available. But the majority of them are equipped with experimental chambers, which limit their applicability only to small‐sized samples. To overcome this limitation, a new instrument named Rainbow X‐Ray (RXR), optimized for large and heavy objects, has been developed at XLab Frascati. Here, we present this unit dedicated to 2D and 3D X‐ray microspectroscopy (both mapping and 'colour' tomography), with a resolution between 25 and 75 μm, depending from the incident energy in the range 800eV–25keV. Copyright © 2015 John Wiley & Sons, Ltd.